Selectivity of tungsten mediated dinitrogen splitting vs. proton reduction - Schluschaß, Bastian; Abbenseth, Josh; Demeshko, Serhiy; Finger, Markus; Franke, Alicja; Herwig, Christian; Würtele, Christian; Ivanovic-Burmazovic, Ivana; Limberg, Christian; Telser, Joshua; Schneider, Sven (Chemical science (Cambridge), 2019)
Mo complexes are currently the most active catalysts for nitrogen fixation under ambient conditions. In comparison, tungsten platforms are scarcely examined. For active catalysts, the control of N 2 vs. proton reduction selectivities remains a difficult task. We here present N 2 splitting using a tungsten pincer platform, which has been proposed as the key reaction for catalytic nitrogen fixation. Starting from [WCl 3 (PNP)] (PNP = N(CH 2 CH 2 P t Bu 2 ) 2 ), the activation of N 2 enabled the isolation of the dinitrogen bridged redox series [(N 2 ){WCl(PNP)} 2 ] 0/+/2+ . Protonation of the neutral complex results either in the formation of a nitride [W(N)Cl( H PNP)] + or H 2 evolution and oxidation of the W 2 N 2 core, respectively, depending on the acid and reaction conditions. Examination of the nitrogen splitting vs. proton reduction selectivity emphasizes the role of hydrogen bonding of the conjugate base with the protonated intermediates and provides guidelines for nitrogen fixation.